Mortality Inequalities and Trends in Low- and Middle-Income Countries,1990-2015. - TABUTIN, Dominique; MASQUELIER, Bruno (Population (1634-2941), 2017)
Between 1990 and 2015, life expectancy increased substantially in most low- and middle-income countries, although progress was very uneven. This article provides an overview of trends in early childhood mortality (0-5 years) and adult mortality (15-60 years) in the 109 low- and middle-income countries with populations of more than one million. It analyses trends in geographical and gender disparities across countries, and patterns of within-country inequalities (education, living standards, place of residence) in ten countries with very different socioeconomic, political and demographic characteristics (Afghanistan, Bolivia, Brazil, Burkina Faso, China, Egypt, India, Indonesia, Nigeria, South Africa). It takes a new look at the epidemiological transition and makes a detailed analysis of AIDS mortality and maternal deaths. Progress has benefited children especially, and often (though not always) women and the most disadvantaged countries or social groups. It would be premature to speak of mortality convergence, however, since despite the progress made, inequalities between and within countries remain large and deserve particular attention from public health policy makers and scientists.